Tolerância de fungos entomopatogênicos e fitopatogênicos a diferentes agentes estressores - (:unkn) unknown (Universidade Brasil, 2020)
In the first chapter, germination, mycelial growth, and conidia production of the entomopathogenic fungi Trichothecium roseum, Metarhizium robertsii, and Metarhizium acridum were studied under conditions of osmotic stress induced by KCl, UV radiation, 4-nitroquinoline-1-oxide (4-NQO), heat, and Congo red. T. roseum is more tolerant than the others when confronting osmotic stress due to KCL, stress due to the 4-NQO, and stress due to Congo Red. However, under UV radiation conditions, Metarhizium species were more tolerant. In summary, we conclude that the fungus T. roseum is a promising agent in the biological control of insects. In the second chapter, the effects of visible light wavelengths on germination, mycelial radial growth, and conidia production of the phytopathogens Colletotrichum acutatum and Fusarium fujikuroi were studied. No differences were found for germination and growth for both fungi under different light and dark regimes; however, significant differences occurred in both conidial production and UV radiation. In the third chapter, differential sensitivities to cell wall stress caused by Congo red were studied in several species of fungi. The saprotrophic fungus Aspergillus niger and the mycoparasitic fungus Trichoderma atroviride stood out as the species most resistant to cell wall stress caused by Congo red, followed by phytopathogenic and other saprotrophic fungi. The insect pathogens exhibited low or moderate tolerance. The insect pathogens Metarhizium acridum and Isaria fumosorosea were the most sensitive.
Keywords: Fungos entomopatogênicos; Fotobiologia; Fungos fitopatogênicos; Fungos saprotróficos; Fungos micoparasitas; Tolerância ao estresse; Engenharia Biomédica (Bioengenharia)